A SYNTACTIC ANALYSIS OF VERB PHRASES IN ELLE'S ARTICLES ON EXOSOME THERAPY AS A NEW BEAUTY TREND - Dewi, Josephine Intan Candra; Sianipar, Laura Angelrich; Wedhowerti, Wedhowerti (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
Skincare has emerged as one of the most frequently discussed topics in both traditional and digital media. Among the latest advancements in aesthetic technology, exosome therapy has become a rising star, gaining significant attention in beauty journalism. With this growing popularity, there arises a need to better understand how information about exosome therapy is conveyed, particularly from a syntactic perspective. This study investigates the types of verb phrases used in three selected articles from ELLE magazine that discuss exosome therapy, aiming to gain a deeper insight into how language is used to inform and persuade readers. Employing a qualitative method and a syntactic approach, the study focuses on fifteen verb phrases found within the texts. The analysis reveals four categories of verb phrases: ditransitive, complex, prepositional, and transitive, with complex and prepositional verb types appearing most frequently. These findings highlight the persuasive and informative function of verb usage in conveying content about exosome therapy clearly and effectively.